C-reactive protein in unstable angina: clinical and angiographic correlation. Issue 1 (3rd December 2010) - Panduranga, Prashanth; Riyami, Abdulla A; Sulaiman, Kadhim J; Mukhaini, Mohammed
Abstract : Objective: To assess prevalence, in-hospital prognostic significance and angiographic correlation of C-reactive protein (CRP) elevation in patients with unstable angina. Design: Prospective observational study. Setting: Royal Hospital, Muscat, Oman. Patients: 100 patients admitted between July 2008 and January 2009. Interventions: Patients with unstable angina and ECG changes without biochemical evidence of necrosis (negative first troponin T), had CRP measured at admission by rate nephelometry (≥10 mg/l abnormal). Main outcome measures: In-hospital cardiac events and severity of coronary artery disease (CAD) in patients with and without CRP elevation. Results: 42% had CRP elevation ≥10 mg/l (Group I), and 58% had levels <10 mg/l (Group II). When compared with Group II, Group I patients had more anginal episodes (mean=4.6±2.5 episodes/patient vs 1.6±2.4; p<0.0001), myocardial infarction (58% vs 17%; p<0.01), in-hospital mortality (9% vs 0%; p=0.03) and severe triple vessel disease (71% vs 24%; p<0.01), and a higher total number of events (86% vs 24%; p<0.0001). Elevated admission CRP as a marker of in-hospital cardiac events showed a sensitivity of 72%, specificity of 88% and positive predictive value of 85%, and, as a marker of significant CAD, showed a specificity of 83% and a positive predictive value of 85%. Conclusions: Raised admission CRP level is predictive of increased in-hospital cardiac events and severe CAD in patients with unstable angina. CRP can be used to risk-stratify unstable angina patients independent of troponin levels. Patients with abnormal CRP should undergo coronary angiography either on-site or transferred to a centre with catheterisation facility during the index hospital admission.